Karakteristik Teh Herbal Daun Kalistemon (Melaleuca viminalis) Berdasarkan Variasi Suhu dan Waktu Pengeringan - Pinasthika Rizkia Warapsari Wiratara; Raida Amelia Ifadah (Jurnal Teknologi dan Industri Pertanian Indonesia, 2022)
Tea is one of the beverages that widely recognized by people in the world. The use of callistemon or commonly known as weeping bottlebrush leaves (Melaleuca viminalis) as herbal tea is a new innovation. Callistemon leaves have functional properties as antioxidants, antibacterial, antifungal and anti-platelet aggregation. The availability of callistemon leaves is quite abundant. The process of callistemon leaves herbal tea using the drying method can affect the quality characteristics. This study has purpose to determine the effect of drying temperature and drying time variation on the quality characteristics of callistemon leaves herbal tea in the form of yield, moisture content, ash content, total phenolic, and antioxidant activity. The research method used was a completely randomized design (CRD) with two factors, namely the drying temperature (50 and 60⁰C) at three levels of drying time, namely 5, 6, and 7 hours. The results showed that the interaction between drying temperature and drying time had a significant effect (P0,01) on the quality characteristics of yield, water content, total phenolic and antioxidant activity of callistemon leaves herbal tea. Meanwhile, the ash content had no significant difference. The best result was obtained from drying treatment at 60 ° C for 7 hours with the characteristics of yield 46.26 ± 1.00%, the water content quality of 6.96 ± 0.62%, ash content of 7.00 ± 0.43%, total phenolic 6.20 ± 0.44 mg AGE/g berat kering matter and antioxidant activity 94.00 ± 0.11%.